Maternidade e vida acadêmica: memórias e narrativas de mães universitárias - OLIVEIRA, Franciele da Silva (2023)
The present study and memorial of life, by title 'Maternity experienced throughout academic life: Memories and narratives of university mothers'', has as general objective to investigate and understand the main challenges faced by five university mothers in reconciling motherhood and academic life. Supported by narrative research, the body of the text dialogues with my experiences as a university mother, since I became a mother during graduation and it was through my experiences that the enthusiasm to write on the subject emerged. The authors who contributed significantly to the theoretical basis of the research were: Elizabeth Batinder (1985), Nancy Chodorow (2002), Laura Gutman (2003), Márcia Neder (2016), Maria Tereza Maldonado (1996). The results of the field research showed that these mothers experience a great burden resulting from the accumulation of responsibilities imposed on women, who in turn need to account for household duties, work and care for their spouse and children, which generates tiredness and physical exhaustion, affecting academic performance. Through the reports, the lack of time to study at home, the absence of the family and university support network, the challenges of locomotion, financial difficulty and the feelings of anguish and distress of mothers in having to leave babies with other people to be able to continue their studies are evidenced.